Dermacentor ticks on wildlife and new records of paralysis - Wilkinson, P. R. (The Entomological Society of British Columbia, 2019)
The second record of paralysis of a mule deer ( Odocoileus hemionus ) by Dermacentor andersoni Stiles resulted from infesting a yearling buck with 50 pairs of ticks. A yearling doe previously infested with D. albipictus was not paralyzed by the same infestation. Spontaneous infestations of wild and captive mule deer include an engorged nymph of D. andersoni . A female of D. andersoni weighing 746 mg was removed from a captive moose ( Alces alces ). Infesting a porcupine ( Erethizon dorsatum ) with about 14,800 larvae of D. andersoni produced more than 600 pairs of adults in the following year. Fifty pairs of D. andersoni applied to the same porcupine yielded a high proportion of engorged females, but the porcupine was not paralyzed. A coyote ( Canis latrans ) and a skunk (Mephitis mephitis) were paralyzed by 50 and 30 pairs of D. andersoni respectively. Few or no larvae or nymphs engorged on the skunk or on two laboratory fitches, whereas many engorged on rabbits used as controls. This suggests that Mustelidae may be resistant or unattractive to immature D. andersoni . Unconfirmed cases of tick paralysis in foxes have been reported. A new record is included of D. andersoni on a marmot ( Marmota monax ).